The Dependence of Caribbean Rainfall on the Interaction of the Tropical Atlantic and Pacific Oceans - Enfield, David B. (1999)
Seasonally stratified analyses of rainfall anomalies over the intra-Americas sea and surrounding land areas and of onset and end dates of the Central American rainy season show that the variability of the tropical Atlantic sea surface temperature anomaly (SSTA) is more strongly associated with rainfall over the Caribbean and Central America than is tropical eastern Pacific SSTA. Seasonal differences include the importance of antisymmetric configurations of tropical Atlantic SSTA in the dry season but not in the rainy season. Both oceans are related to rainfall, but the strength of the rainfall response appears to depend on how SSTA in the tropical Atlantic and eastern Pacific combine. The strongest response occurs when the tropical Atlantic is in the configuration of a meridional dipole (antisymmetric across the ITCZ) and the eastern tropical Pacific is of opposite sign to the tropical North Atlantic. When the tropical North Atlantic and tropical Pacific are of the same sign, the rainfall response is weaker. The rainy season in lower Central America tends to start early and end late in years that begin with warm SSTs in the tropical North Atlantic, and the end dates are also delayed when the eastern equatorial Pacific is cool. This enhancement of date departures for zonally antisymmetric configurations of SSTA between the North Atlantic and Pacific is qualitatively consistent with the results for rainfall anomalies.